Displacement measurement of concrete bridges by the sampling Moiré method based on phase analysis of repeated pattern. (22nd April 2020) - Ri, S.; Wang, Q.; Tsuda, H.; Shirasaki, H.; Kuribayashi, K.
Abstract: Measuring accurate deformation distribution of large‐scale structures inexpensively and efficiently is a crucial challenge of structural health monitoring. Phase‐based imaging technique has great potential for accurate and robust multipoint displacement measurement in the field. In this study, the sampling Moiré method—one of the promising optical techniques—was applied to the displacement measurement of a concrete bridge for the high‐speed railway in Japan. Using retroreflective Moiré markers, the two‐dimensional in‐plane displacements at multiple locations could be easily measured from recorded digital images at a distance of 20 m regardless of day and night. Results of the dynamic deflection obtained from the sampling Moiré method were in good agreement with those from a conventional laser Doppler vibrometer. The time series of two‐dimensional displacement analyses when the outbound or inbound trains passed at the speed of 150 or 320 km/h through the bridge revealed that the points at the centre and the quarter of the bridge span demonstrated complex deformation behaviour showing elliptical rotation. The effects of random noise of the recorded image were quantitatively investigated, and the air fluctuation was discussed from the field experiments. We proved that measurements using the sampling Moiré method could be more stable at night than daytime.